-24+3k=k-2k

Simple and best practice solution for -24+3k=k-2k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -24+3k=k-2k equation:


Simplifying
-24 + 3k = k + -2k

Combine like terms: k + -2k = -1k
-24 + 3k = -1k

Solving
-24 + 3k = -1k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add 'k' to each side of the equation.
-24 + 3k + k = -1k + k

Combine like terms: 3k + k = 4k
-24 + 4k = -1k + k

Combine like terms: -1k + k = 0
-24 + 4k = 0

Add '24' to each side of the equation.
-24 + 24 + 4k = 0 + 24

Combine like terms: -24 + 24 = 0
0 + 4k = 0 + 24
4k = 0 + 24

Combine like terms: 0 + 24 = 24
4k = 24

Divide each side by '4'.
k = 6

Simplifying
k = 6

See similar equations:

| (4x^2)+16x+13=0 | | 13.7v-6.5=-2.3+8.3 | | n^2=-5n | | 2(x+4)-5x+7= | | 0=-6(y+2) | | 5=4(x-2)+9 | | 7+6x=-4(x-5)+7 | | 12-1.2(x-5)=22-2(x-4) | | -4(t+6)=4 | | -3-8x+5x=4-4x | | n^2+6n=-5 | | 3k+8k=8k-9 | | 5(x-7)+2=-28 | | 3x+5=3(x-9) | | -5(z+7)=-6z | | x*2-x=12 | | 5n-4(n-6)=2+2n | | 10-(3y-3)=2-4y | | x/8-1=-5 | | 2x*2-x=45 | | 3xy^2-2xy+2=-3y^2+y+4x | | 10-4(x-5)=11-x | | 4v^2-4v=15v | | h=4f | | x^2-20x=-53 | | -4x-9+3(2x+5)-2= | | (-7x+2)-(-6x-5)=3 | | 12(t-2)+6t=6(3t+3)-12 | | 3b=11b | | 7[3-(8x-3)]+4x=0 | | 3x^2+10x-32=0 | | x^2=-14x-24 |

Equations solver categories